Determinants of the decline in mortality from acute myocardial infarction in England between 2002 and 2010: linked national database study. - Smolina, K; Wright, F; Rayner, M; Goldacre, M (2012)
OBJECTIVE: To report trends in event and case fatality rates for acute myocardial infarction and examine the relative contributions of changes in these rates to changes in total mortality from acute myocardial infarction by sex, age, and geographical region between 2002 and 2010. DESIGN: Population based study using person linked routine hospital and mortality data. SETTING: England. PARTICIPANTS: 840,175 people of all ages who were admitted to hospital for acute myocardial infarction or died suddenly from acute myocardial infarction. MAIN OUTCOME MEASURES: Acute myocardial infarction event, 30 day case fatality, and total mortality rates. RESULTS: From 2002 to 2010 in England, the age standardised total mortality rate fell by about half, whereas the age standardised event and case fatality rates both declined by about one third. In men, the acute myocardial infarction event, case fatality, and total mortality rates declined at an average annual rate of, respectively, 4.8% (95% confidence interval 3.0% to 6.5%), 3.6% (3.4% to 3.7%), and 8.6% (5.4% to 11.6%). In women, the corresponding figures were 4.5% (1.7% to 7.1%), 4.2% (4.0% to 4.3%), and 9.1% (4.5% to 13.6%). Overall, the relative contributions of the reductions in event and case fatality rates to the decline in acute myocardial infarction mortality rate were, respectively, 57% and 43% in men and 52% and 48% in women; however, the relative contributions differed by age, sex, and geographical region. CONCLUSIONS: Just over half of the decline in deaths from acute myocardial infarction during the 2000s in England can be attributed to a decline in event rate and just less than half to improved survival at 30 days. Both prevention of acute myocardial infarction and acute medical treatment have contributed to the decline in deaths from acute myocardial infarction over the past decade.